Aortic valve replacement with right thoracotomy in a patient withsternal metastasis from renal carcinoma - Moraldi, A.; Nicolini, F.; Berghi, C.; Agostinelli, et al., A. (Acta Biomedica Atenei Parmensis, 2009)
We present a clinical case of severe aortic stenosis in a 73 years old patient symptomatic for dispnoea class NYHA III-IV. At the physical examination the patient presented a single sternal metastasis of renal carcinoma involving the sternum. Oncological stability prompted us to perform aortic valve replacement. In order to avoid median sternotomy and its complications due to the presence of sternal metastasis we successfully performed aortic valve replacement through a right minithoracotomy.